Influence of Mobile Charges in the Substrate of BAW Filters on High Resistivity Silicon. - Hagelauer, Amelie Marietta; Bader, Bernhard; Henn, G.; Schaeufele, A.; Marksteiner, Stefan; Wagner, Karl Christian; Weigel, Robert (International Ultrasonics Symposium, 2009)
BAW (bulk acoustic wave) filters have emerged as an important technology for GHz filtering components. Especially the high quality factor and the good temperature coefficient make BAW filters well suited for W-CDMA band 2 and band 3 devices. During the design phase it is essential to analyze and minimize possible loss mechanisms to meet the high requirements of these devices. Well known loss mechanisms are metal conductivity, viscosity and acoustic losses. A less well known loss mechanism is the existence of mobile charges at the surface of high resistivity silicon. This loss effect appears between the silicon substrate and the first silicon dioxide layer of the BAW structure. Induced charges increase the insertion loss and influence the performance of BAW filters. The two methods that are most promising for BAW applications to minimize the effect are ion implantation and the use of low charge silicon-dioxide. The aim of this work is the investigation and comparison of the mentioned methods in case of mirror-type BAW filters. We describe the loss mechanism, its counter measures and the impact on the filter performance. Therefore we designed test filters and test structures, manufactured on several test wafers. Additionally we used EM-simulations to evaluate the measurements of our test structures. An extended filter simulation model reflects the measured insertion attenuation of the filter performance pretty well.
elib2cris::1512001600,hagelauer2009a
Keywords: BAW filter substrate; EM-simulations; GHz filtering components; W-CDMA band 2 devices; W-CDMA band 3 devices; bulk acoustic wave filters; extended filter simulation model; first silicon dioxide layer; high resistivity silicon; induced charges; insertion attenuation; insertion loss; ion implantation; loss mechanisms; low charge silicon dioxid; mirror-type BAW filters; silicon substrate; surface mobile charges; bulk acoustic wave devices; code division multiple access; dielectric losses; elemental semiconductors; radiofrequency filters; silicon; substrates; surface acoustic wave filters; surface charging